AB0666 Clinical and serological outcomes of patients with giant cell arteritis treated with tocilizumab or abatacept as steroid-sparing agents. (12th June 2018) - Rossi, D.; Cecchi, I.; Rubini, E.; Radin, M.; Sciascia, S.; Roccatello, D.
Abstract : Background: Giant cell arteritis (GCA) is a common form of systemic vasculitis. The current mainstay of GCA management is glucocorticoid (GC) therapy. Recently, at least 2 biological therapies [tocilizumab (TCZ) and abatacept (ABA)] have been proven to be effective in the management of CGA in randomised controlled trials. Nevertheless, their use as steroid sparing agents might need further investigation. Objectives: We aimed to investigate the steroid-sparing effect of biological therapies, namely TCZ and ABA, in a cohort of GCA patients when compared to standard GC treatment. Methods: We retrospectively collected data from GCA patients who attended the S.G. Bosco Hospital, Turin, Italy, who were treated with TCZ, both intravenous (IV) and subcutaneous (SC), and/or ABA SC (8 mg/kg/month, 162 mg/week, and 125 mg/week respectively). These therapies were prescribed as first line agents or as second line when patients were refractory/intolerant/contraindicated to standard immunosuppressive therapies. Complete response to the treatment was define as a clinical and serological remission after 12 months of therapy; partial response was defined as clinical or serological remission after 12 months of therapy. Results: This retrospective study included 33 GCA patients [mean age 74 (range 85–57), females 63%, mean follow-up from GCA diagnosis 44.4±33.5 months). Table 1 resumes the characteristics of the GCA patients included in the study. Twenty-eight patients out of 33 (85%) received one biologic agent. Five patients (15%) needed a therapeutic switch (one patient from TCZ to ABA, and 4 patients from ABA to TCZ). Patients were treated as follow: 9 with TCZ IV, 11 with TCZ SC, and 18 with ABA. Among the TCZ IV group, all patients experienced a response (57% complete response, and 43% partial response). Among the TCZ SC group, 83% experienced a response (67% complete response, and 16% partial response). Among the ABA group, 86% experienced a response (36% complete response and 50% partial response). After 12 months of therapy, 100% of patients in TCZ groups, both IV and SC, and 64.2% of ABA group were treated with low doses of oral prednisone (≤7.5 mg/day) as maintenance. We noticed a significant reduction of inflammatory parameters [C-reactive protein (CRP) and erythrocyte sedimentation rate (ESR)] after 12 months of therapy with TCZ [TCZ IV group: mean baseline CRP (mg/dl) 1.9±2.3, mean CRP after 12 months of therapy 0, 3±0.2; mean baseline ESR (mm/h) 58.1±25.6, mean ESR after 12 months 9.5±4.2; TCZ SC group: mean baseline CRP 4.5±3.8, mean CRP after 12 months 0.2±0.2; mean baseline ESR 51.9±27, mean ESR after 12 months 6.5±6]. When compared to standard GC regimen, 1 in patients treated with TCZ, both IV and SC, we estimated a median steroid-sparing effect quantifiable in 30 mg/daily in the first month and an overall steroid-sparing effect of 15 mg/daily when assessed in 12 months. Conclusions: This retrospective study confirms the efficacy of biological therapies in the management of CGA. Besides, in our experience TCZ allowed a significant reduction of GCs use, especially in the first month of therapy, when compared to standard GCs-based regimens. Reference: [1] Dasgupta B, et al. BSR and BHPR Standards, Guidelines and Audit Working Group. BSR and BHPR guidelines for the management of giant cell arteritis. Rheumatology. 2010Aug;49(8):1594–7. Disclosure of Interest: None declared